Mathematical Optimization Theory and Operations Research: Recent Trends 21st International Conference, MOTOR 2022, Petrozavodsk, Russia, July 2-6, 2022, Revised Selected Papers - Kochetov, Yury.; Eremeev, Anton; Khamisov, Oleg.; Rettieva, Anna. (Cham : Springer Nature Switzerland : Imprint: Springer, 2022)
This book constitutes refereed proceedings of the 21st International Conference on Mathematical Optimization Theory and Operations Research, MOTOR 2022, held in Petrozavodsk, Russia, in July 2022. The 21 full papers and 3 short papers presented in this volume were carefully reviewed and selected from a total of 88 submissions. The papers in the volume are organised according to the following topical headings: invited talks; integer programming and combinatorial optimization; mathematical programming; game theory and optimal control; operational research applications.
Invited Talks -- Integer Programming and Combinatorial Optimization -- Mathematical Programming -- Game Theory and Optimal Control -- Operational Research Applications.
Keywords: Computer science-Mathematics.; Data structures (Computer science).; Information theory; Discrete mathematics; Numerical analysis; Algorithms; Artificial intelligence; Mathematical Applications in Computer Science; Data Structures and Information Theory; Discrete Mathematics in Computer Science; Numerical Analysis; Algorithms; Artificial Intelligence